Wirausaha Pemula Dengan Pemanfaatan Bahan Alami Pembuatan Ecoprint Pada Kelompok Tani di Koya Koso Kota Jayapura - Ratang, Westim; Rante, Yohanis; Salle, Hesty T.; Wandimbo, Rosita (The Community Engagement Journal, 2024)
Ecoprint coloring technique is a category of stamping coloring techniques. The material used is usually in the form of plants can be leaves, flowers, stems, and roots that have certain criteria. One plant that can be used is leaves with downy criteria on the surface like teak leaves. To produce good ecoprint colors, you must consider the ecoprint dyeing technique, the type of textile material used, the type of fixation agent, the mass of the fixation substance to the length of the dyeing process. Alternative problem solving is done by conducting training in dyeing and ecoprinting so that farmers know and are able to utilize materials in the environment around Koya Koso and provide skills and mastery of small business management. The target in this service is a farmer group in Koya Koso through beginner entrepreneur training by utilizing natural materials for making ecoprints in farmer groups in Koya Koso, Jayapura City. Keywords: Beginner Hero, Eco Print, Koya Koso